Africa RISING - A Two Year Cereal Legume in Northern Ghana - International Institute of Tropical Agriculture; Ministry of Food and Agriculture, Government of Ghana; Savanna Agricultural Research Institute (International Food Policy Research Institute, 2016)
This study contains data from different cereal legume rotation systems in northern Ghana. Project title: A Two Year Cereal Legume Rotation in Northern Ghana Project abstract: This project compares different cereal legume rotation systems and determines farmers' preferences. Project website: http://africa-rising.net http://africa-rising.net/where-we-work/west-africa/